2011
DOI: 10.1007/s11106-011-9311-3
|View full text |Cite
|
Sign up to set email alerts
|

The key metallurgical features of selective laser melting of stainless steel powder for building metallic part

Abstract: UDC 621.762 316L stainless steel parts are manufactured via selective laser melting. The investigation into the main characteristics and metallurgical mechanisms of selective laser melting process are highlighted in this work. The morphologies, microstructures and elemental compositions of as received scan tracks and samples are detected through optical microscope, SEM and energy dispersive X-ray spectroscopy respectively. The morphology of melted track exhibits scaly figures from top view, which is similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The architecture of this layer particle for coarse powder is illustrated in Figure 6 with void area and hollow powder. There is a large void between each particle; meanwhile, the number of hollow powders increased along with the increasing powder particle size [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Therefore, the layer thickness relative density of coarse powder is relatively low, and more gas components are contained in the powder layer.…”
Section: Resultsmentioning
confidence: 99%
“…The architecture of this layer particle for coarse powder is illustrated in Figure 6 with void area and hollow powder. There is a large void between each particle; meanwhile, the number of hollow powders increased along with the increasing powder particle size [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Therefore, the layer thickness relative density of coarse powder is relatively low, and more gas components are contained in the powder layer.…”
Section: Resultsmentioning
confidence: 99%
“…The previous schematic ( Figure 1) is a depiction of the LM process. Although LM is typically used for the fabrication of parts from metallic powders (Abe et al, 2001;Bertrand et al, 2007;Li et al, 2011;) this AM technique was identified as potentially being able to process the regolith ceramic material.…”
Section: Methodsmentioning
confidence: 99%
“…3b); and (c) when the energy density is excessively low, a series of barely connected metal beads, balling, is observed ( Fig. 3c) (Li et al, 2011;Tolochko et al, 2004). When producing AM parts, only the continuous regime is desired, as this track shape usually leads to good bonding between adjacent lines and results in minimal porosity within the final part.…”
Section: Track Morphologymentioning
confidence: 99%